Design a quick connector for endoscopic surgical robots - Chua, Nicholas Ming Hao (Nanyang Technological University, 2024)
This report is written for the Final Year Project A130, titled “Design a Quick Connector for Endoscopic Surgical Robots”. It provides a comprehensive overview of prototype development of a quick connector for a novel surgical robot system. At this stage, a one Degree of Freedom (DOF) motion study is mainly discussed for the proposed connector. As each DOF is controlled by two motors, to include additional motors enables the extension of the connector for instruments with multiple DOFs. Engineering design concepts and calculations that culminated in the development of the prototype are presented in this report, followed by a comprehensive discussion of the motor communication and programming aspect. Finally, experimental results validating the functionality and reliability of the quick connector prototype was evaluated.